Cardiorespiratory Alterations Following Acute Normovolemic Hemodilution in a Pediatric and an Adult Porcine Model: A Prospective Interventional Study. (March 2018) - Albu, Gergely; Sottas, Cédric; Dolci, Mirko; Walesa, Magali; Peták, Ferenc; Habre, Walid
Abstract : BACKGROUND: Acute normovolemic hemodilution (ANH) is considered as a blood-sparing intervention during the perioperative management. We aimed at comparing the cardiopulmonary consequences of ANH between adult pigs and weaned piglets to establish the effects of lowering hematocrit in these age groups, and thereby testing the hypothesis that difference in the age-related physiological behavior will be reflected in the cardiorespiratory changes following ANH. METHODS: ANH was achieved in anesthetized, mechanically ventilated adult minipigs and 5-week-old weaned piglets by stepwise blood withdrawal (10 mL/kg) with crystalloids replacement. Cardiorespiratory assessments consisted of measuring airway resistance, respiratory tissue elastance, effective lung volume, extravascular lung water, mean arterial pressure, pulmonary blood flow, and cardiac output. Respiratory and hemodynamic measurements were made at control conditions and following each ANH condition obtained with 5 to 7 steps. RESULTS: ANH induced immediate and progressive increases in airway resistance and tissue elastance in both groups, with more pronounced worsening in adults despite the similar decreases in hematocrit. The increases in extravascular lung water were significantly greater in the adult population with the differences in mean (DM) of 25.1% (95% confidence interval [CI], 5.3%–44.9%). Progressive ANH led to significant decreases in the DM of pulmonary blood flow (45.3%; 95% CI, 19.8%–70.8%) and mean arterial pressure (36.3%; 95% CI, 18.7%–53.9%) only in adults, whereas cardiac output increased significantly only in the piglets (DM, 51.6; 95% CI, 14.2%–89.0%). CONCLUSIONS: While ANH led to mild detrimental cardiorespiratory changes in weaned piglets, gradual developments of bronchoconstriction, lung tissue extravasation and stiffening, and deteriorations in systemic and pulmonary hemodynamics were observed in adults. ANH may exert age-dependent cardiorespiratory effect.